Seeing the forest through the trees: improving decision making on the Iowa gambling task by shifting focus from short- to long-term outcomes - Buelow, Melissa T.; Okdie, Bradley M.; Blaine, Amber L. (Frontiers in Psychology, 2013)
Introduction: The present study sought to examine two methods by which to improve decision making on the Iowa Gambling Task (IGT): inducing a negative mood and providing additional learning trials. Method: In the first study, 194 undergraduate students (74 male; Mage = 19.44 [SD = 3.69]) were randomly assigned to view a series of pictures to induce a positive, negative, or neutral mood immediately prior to the IGT. In the second study, 276 undergraduate students (111 male; Mage = 19.18 [SD = 2.58]) completed a delay discounting task and back-to-back administrations of the IGT. Results: Participants in an induced negative mood selected more from Deck C during the final trials than those in an induced positive mood. Providing additional learning trials resulted in better decision making: participants shifted their focus from the frequency of immediate gains/losses (i.e., a preference for Decks B and D) to long-term outcomes (i.e., a preference for Deck D). In addition, disadvantageous decision making on the additional learning trials was associated with larger delay discounting (i.e., a preference for more immediate but smaller rewards). Conclusions: The present results indicate that decision making is affected by negative mood state, and that decision making can be improved by increasing the number of learning trials. In addition, the current results provide evidence of a relationship between performance on the IGT and on a separate measure of decision making, the delay discounting task. Moreover, the present results indicate that improved decision making on the IGT can be attributed to shifting focus towards long-term outcomes, as evidenced by increased selections from advantageous decks as well as correlations between the IGT and delay discounting task. Implications for the assessment of decision making using the IGT are discussed.